The world and all that it holds - Hemon, Aleksandar, 1964- (New York : MCD/Farrar, Straus and Giroux, 2023)
"From literary powerhouse Aleksandar Hemon, author of The Lazarus Project, comes a big, brilliant, sweeping novel of love, memory, and history in the making. It tells of the relationship between Pinto and Osman, who cross the battlefields of the First World War, find love, and fight to survive"--
Keywords: Novels